Maksimasi Keuntungan Layanan Jasa Be Clean Laundry Dengan Menerapkan Metode Branch And Bound - Syahputra, Bayu Teza; Lubis, Riri Syafitri; Cipta, Hendra (Zeta - Math Journal, 2021)
The purpose of this research is to find the maximize benefits from Be Clean Laundry business. In optimize laundry business by looking at the limited resources of the business used branch and bound method. Using the branch and bound method assisted by QM software in more optimal laundry, coat 53 kg, doll 32 kg, blanket 95 kg, bedcover 105 kg, gordyn 91 kg, and clothes 805 kg with a profit of Rp. 4.027.000, while the previous profit based on estimate made by the laundry Owner of Rp. 4.000.000 increase of 0,7 %.